Validitas Instrumen Pengembangan Video Pembelajaran Matematika Berbasis Software Wondershare Filmora Untuk Meningkatkan Minat Belajar Peserta Didik Materi Penyajian Didik Kelas VII SMP/MTs - Risali, Hafizah; Zulfah, Zulfah; Rizki, Lussy Midani (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This research is based on the problems that exist in schools namely the lack of student interest in learning mathematics and this requires an innovation of learning media used in schools during the teaching and learning process. This study aims to produce quality instrument validation that will be used in assessing mathematics learning videos based on the wondershare filmora software. This development research uses the Plomp model. The Plomp model consists of 3 stages, preliminary research, prototyping stage and assessment stage. The subjects of this research are 3 expert validators who are competent in their respective fields. This study uses instrument validity, practicality and effectiveness. The research data were collected using observation sheets, interviews and questionnaires. The data analysis techniques used are preliminary data analysis, data validity analysis, data practicality analysis, and data effectiveness analysis. the results of the assessment sheet of interview questions, observations and questionnaires using instrument validation state that these three things are in the very valid category, so that interviews, observations and questionnaires have been used to obtain data and information on the study.